2002
DOI: 10.1086/340024
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double‐Blind, Placebo‐Controlled Trial of Dexamethasone in Severe Respiratory Syncytial Virus (RSV) Infection: Effects on RSV Quantity and Clinical Outcome

Abstract: Forty-one previously healthy children <2 years of age who required mechanical ventilation for respiratory syncytial virus (RSV) infection were randomized to receive dexamethasone (0.5 mg/kg; n=22) or saline placebo (n=19) intravenously every 12 h for 4 days. RSV quantity was measured by quantitative plaque assay in fresh tracheal and nasal aspirates obtained at intervals of 24+/-3 h on days 0, 1, 2, 5, and 7 following entry. Analysis by linear mixed-effects modeling demonstrated a significantly greater decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 20 publications
3
81
0
Order By: Relevance
“…Yet, post-hoc analysis suggested that corticosteroids might be beneficial among ventilated infants who met criteria for mild disease as derived by Tasker et al (Tasker et al, 2000). Similar results were obtained in a study including 41 mechanically ventilated infants (Buckingham et al, 2002). Recently, Van Woensel et al have completed a third RCT (the so-called STAR-trial) based upon the posthoc analysis from their second RCT (van Woensel et al, 2011).…”
Section: Treatment Of Severe Rsv Lrtdmentioning
confidence: 54%
See 1 more Smart Citation
“…Yet, post-hoc analysis suggested that corticosteroids might be beneficial among ventilated infants who met criteria for mild disease as derived by Tasker et al (Tasker et al, 2000). Similar results were obtained in a study including 41 mechanically ventilated infants (Buckingham et al, 2002). Recently, Van Woensel et al have completed a third RCT (the so-called STAR-trial) based upon the posthoc analysis from their second RCT (van Woensel et al, 2011).…”
Section: Treatment Of Severe Rsv Lrtdmentioning
confidence: 54%
“…Others have explored the efficiacy of corticosteroids (Buckingham et al, 2002;van Woensel et al, 1997;van Woensel et al, 2003b;van Woensel et al, 2011). Unfortunately, the results of these studies cannot be easily compared because of the different dosing and duration of treatment.…”
Section: Treatment Of Severe Rsv Lrtdmentioning
confidence: 99%
“…Infant RSV pathogenesis seems to be driven mainly by a rapid and profound viral replication and the ineffectiveness of an adaptive immune response to limit the infection. Moreover, treatment of RSV disease in infants with corticosteroids seems to be ineffectual (Buckingham et al, 2002;Ermers et al, 2009), and a correlation has been demonstrated between the quantity of RSV in the respiratory tract of infants and disease severity (Buckingham et al, 2000;DeVincenzo et al, 2005). A recent study in experimentally infected adults with RSV demonstrated a close correlation between viral load and manifestation of disease symptoms (DeVincenzo et al, 2010).…”
Section: Disease Driversmentioning
confidence: 99%
“…Systemic administration of prednisolone and topical application of fluticasone, budesonide, and deoxiribonuclease I were ineffective (Bulow et al, 1999;Cade et al, 2000;Nasr et al, 2001;Wong et al, 2000). Intravenous dexamethasone had little effect, although when the drug was received by inhalation, patients hospital stay seemed to be reduced (Bentur et al, 2005;Buckingham et al, 2002). Recent data however illustrate that, at least in children, severe forms of RSV disease are related to inadequate rather than hyperresponsive immune reactions (DeVincenzo, 2007;Welliver, 2008).…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%
“…Overall, however, corticosteroids have not been demonstrated to have clinically significant effects in acute RSV infection, regardless of the method of administration (Roosevelt et al 1996;Klassen et al 1996;De Boeck et al 1997;Richter & Seddon 1998;Bulow et al 1999) or the severity of the infants' RSV illness (Buckingham et al 2002). Indeed, in ventilated infants, intravenous dexamethasone did not result in a significant reduction in the duration of mechanical ventilation, length of stay in the paediatric intensive care unit, hospital stay or the duration of supplementary oxygen administration (Van Woensel et al 2003).…”
Section: Adrenaline (Epineprine) Adrenaline (Epineprine) Is Anmentioning
confidence: 99%